Mechanisms of Therapeutic Resistance in Cancer (Stem) Cells with Emphasis on Thyroid Cancer Cells - Hombach-Klonisch, Sabine; Natarajan, Suchitra; Thanasupawat, Thatchawan; Medapati, Manoj R.; Pathak, Alok; Ghavami, Saeid; Klonisch, Thomas (Frontiers in Endocrinology, 2014)
The two main reasons for death of cancer patients, tumor recurrence and metastasis, are multi-stage cellular processes that involve increased cell plasticity and coincide with elevated resistance to anti-cancer treatments. Epithelial-to-mesenchymal transition (EMT) is a key contributor to metastasis in many cancer types, including thyroid cancer and is known to confer stem cell-like properties onto cancer cells. This review provides an overview of molecular mechanisms and factors known to contribute to cancer cell plasticity and capable of enhancing cancer cell resistance to radio- and chemotherapy. We elucidate the role of DNA repair mechanisms in contributing to therapeutic resistance, with a special emphasis on thyroid cancer. Next, we explore the emerging roles of autophagy and damage-associated molecular pattern responses in EMT and chemoresistance in tumor cells. Finally, we demonstrate how cancer cells, including thyroid cancer cells, can highjack the oncofetal nucleoprotein high-mobility group A2 to gain increased transformative cell plasticity, prevent apoptosis, and enhance metastasis of chemoresistant tumor cells.